Брендинг регіонів України: мотиваційні акценти та стратегічні орієнтири - Оксенюк, Катерина Ігорівна (Одеса : Гельветика, 2025)
У статті розглядаються ключові підходи до брендингу регіонів України з урахуванням мотиваційних акцентів, що впливають на формування позитивного іміджу територій та стратегічний розвиток. Особлива увага приділена ролі мотивації у залученні інвестицій, розвитку туризму та підвищенні конкурентоспроможності регіонів. Наведено мотиваційні чинники, що впливають на ефективність бренду території: емоційна залученість, гордість за місце проживання, можливості самореалізації, локальна ідентичність, відкритість до інновацій, рівень сервісу та екологічна свідомість. Запропоновано типологізацію стратегічних орієнтирів бренду регіону. Окреслено важливість взаємодії органів влади, бізнесу та громади у розробці й реалізації ефективних бренд стратегій. Доведено, що регіональний брендинг є потужним інструментом економічної активації територій.

The article explores contemporary approaches to the formation of regional brands in Ukraine, taking into account motivational aspects and strategic guidelines. It emphasizes that regional branding, in the context of European integration and globalization, serves not only as a tool of territorial marketing but also as a factor in enhancing investment attractiveness, strengthening the internal identity of the population, and shaping a positive image both domestically and internationally. The author highlights the need for a motivational reorientation within the system of regional governance, where a brand should not only communicate the uniqueness of a territory but also inspire various target audiences – residents, entrepreneurs, tourists, investors, and youth – to participate in regional development. The article identifies key motivational factors that influence the effectiveness of territorial branding: emotional engagement, pride in one’s place of residence, opportunities for self-realization, local identity, openness to innovation, quality of services, and environmental awareness. Motivational accents that are crucial to building a successful brand are outlined. These include: pride in the region and a sense of belonging; opportunities for personal and professional fulfillment; comfort, safety, and quality of life; access to education, culture, and infrastructure; emotional perception of space; local identity; participation in the co-creation of the region’s future; openness to innovation; environmental consciousness; and the brand’s value orientation toward sustainable development. The article underscores the importance of cooperation among authorities, businesses, and communities in the development and implementation of effective branding strategies. It argues that regional branding is a powerful tool for economic activation of territories, contributing to capital inflows, the development of entrepreneurship, and the creation of added value at the local level. Strategic guidelines of regional branding are defined as instruments for realizing long-term visions of the regions. A typology of strategic orientations is proposed, encompassing six key directions: investment-industrial orientation; tourism-cultural orientation; ecological-landscape orientation; agro-cluster orientation; innovation-educational orientation; and socio-humanitarian orientation. The article concludes that a regional brand grounded in motivational accents and strategically oriented is not merely a promotional tool but, above all, a platform for shaping the region’s future, enhancing its competitiveness, social cohesion, and sustainable development.
Branding of Ukrainian regions: motivational emphases and strategic guidelines
Keywords: мотивація; регіон; брендинг; ідентичність території; регіональний брендинг; імідж регіону; стратегія розвитку; цінності бренду.